The Complexities of Law Interpretation with Regard to the International Criminal Court - Głogowska, Sonia (Comparative Law Review, 2019)
This article addresses one of the challenges faced by judges of the International Criminal Court, namely the interpretation of applicable legal provisions. The incompleteness of the Rome Statute, uncertainty as to the binding nature of relevant regulations, numerous general clauses – these are just some of the difficulties observed in the interpretation process. The aim of this short publication is to show the directives and types of interpretation used by the International Criminal Court, with particular reference to factors determining the process of interpretation. This article includes, inter alia, the analysis of relevant regulations, especially the Rome Statute and the Vienna Convention on the Law of Treaties, as well as the case law of the International Criminal Court. Considerations presented in this work are aimed at showing the specific character of interpretation conducted by the International Criminal Court.